Analisis Break Even Point Usaha Tahu Tempe “Pak Rahmad” di Desa Ongkaw, Kecamatan Sinonsayang, Kabupaten Minahasa Selatan - Lepa, Kevin Mirachel; Rengkung, Leonardus Ricky; Wariki, Barce Andries Feriano (Journal of Agribusiness and Rural Development (Jurnal Agribisnis dan Pengembangan Pedesaan), 2025)
This study aims to analyze the Break Even Point (BEP) of Pak Rahmad’s Tempe Tofu Business in Ongkaw Village, Sinonsayang District, South Minahasa Regency. The research was conducted from October to December 2023. Data collection techniques using survey methods, data obtained through interview activities and direct observation at the research site. The data analysis method uses the Break Even Point method. The results of the study obtained the calculation of the BEP in the tofu tempeh business “Pak Rahmad”, in 2023 the break-even point of tofu sales was at IDR 20,689,913 while the break-even point of the unit was at 52,672 pcs, while the break-even point of Tempeh sales was at IDR 3,274,910 and the BEP unit was at 1,637pcs.